Combination of PIPRECIA-S and Complex Proportional Assessment Approaches for Selecting MSME Locations - Sah, Andrian; Indra, Indra; Erkamim, Moh.; Rahmadian, Jefri (Jurnal Ilmu Komputer; Vol 18 No 1 (2025): Jurnal Ilmu KomputerDO - 10.24843/JIK.2025.v18.i01.p01, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, but selecting a strategic business location often becomes a major challenge for MSME owners. The right location can determine business success, while poor decision-making is often due to subjectivity and limited data in manual processes. This study develops a Decision Support System (DSS) for MSME location selection by combining the Complex Proportional Assessment (COPRAS) method and the Simplified Pivot Pairwise Relative Criteria Importance Assessment (PIPRECIA-S) weighting technique. COPRAS was chosen for its ability to comprehensively evaluate alternatives based on complex criteria, while PIPRECIA-S was used to determine the criteria weights more systematically and effectively. The system is web-based, enabling the management of criteria, alternatives, and alternative evaluations to generate recommendations for business location rankings. The results of the black-box testing revealed that all core system functions operate smoothly and meet the specified requirements. This indicates that the system runs efficiently and fulfills all the intended functionalities.